Influence of Organizational Culture, Compensation, and Work Stress on the Employee Performance of an Islamic Small Banking - Rifka Ulfa Hanifah; Ani Muttaqiyatun; Ifta Firdausa Nuzula (The Indonesian Institute of Science and Technology Research, 2022)
This study aims to determine the effect of organizational culture, compensation, and work stress on employee performance at small Islamic banking in Yogyakarta, Indonesia. The independent variables in this research are Organizational Culture, Compensation and Job Stress. The dependent variable in this study is the performance of employees. The population in this study were 60 employees. This study uses the sampling technique fed up with taking all part in the organization. The type of data used is primary data. Data is obtained directly at the source or object of research by distributing data questionnaires. From the results of panel data regression analysis with a significant level of 5%, it can be concluded that the first hypothesis of Organizational Culture has a positive and significant effect on Employee Performance with a sig value of 0.011. The second compensation hypothesis positively and significantly impacts employee performance with a sig value of 0.001. The third hypothesis is that work stress has a negative and significant impact on the employee performance, with a score sig 0.005. And the fourth hypothesis is that Organizational Culture, Compensation and work stress simultaneously affect the performance of employees with a sig value of 0.000.